Effects of Fungicides, Time of Application, and Application Method on Control of Sclerotinia Blight in Peanut - Jason E. Woodward; Scott A. Russell; Michael R. Baring; John M. Cason; Todd A. Baughman (International Journal of Agronomy)
Field studies were conducted from 2007 to 2010 to evaluate the response of peanut cultivars to different fungicides, application timings, and methods. Overall, fungicides reduced Sclerotinia blight incidence and increased pod yields when applied to susceptible and partially resistant cultivars. Disease suppression was greater when full fungicide rates were applied preventatively; however, yields between fungicide treated plots were similar. Lower levels of disease and higher yields were achieved with the partially resistant cultivar Tamrun OL07 compared to the susceptible cultivars Flavor Runner 458 and Tamrun OL 02. Despite possessing improved resistance Tamrun OL07 responded to all fungicide applications. While similar levels of disease control were achieved with broadcast or banded applications made during the day or at night, the yield response for the different application methods was inconsistent among years. A negative relationship (slope = −73.8; R2=0.73; P<0.01) was observed between final disease incidence ratings and yield data from studies where a fungicide response was observed. These studies suggest that both boscalid and fluazinam are effective at controlling Sclerotinia blight in peanuts. Alternative management strategies such as nighttime and banded applications could allow for lower fungicide rates to be used; however, additional studies are warranted.